2017
DOI: 10.1080/01596306.2017.1312284
|View full text |Cite
|
Sign up to set email alerts
|

Shifting discourses from boy preference to boy crisis: educating boys and nation building in neoliberal China

Abstract: It is well established that China has emerged as a major economic power, resulting from the nationÕs neoliberal modernisation. What is less understood is the socio-cultural and educational impact of this change on public institutions. This article focuses on the education system, which is currently seen as central to delivering the nationÕs modernisation project, particularly through suzhi jiaoyu (education for quality). More specifically, we engage with a pervasive public discourse of a boy crisis. We suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…He believed that buying a fangzi (house/apartment) would enable him to make a masculine achievement as a father through passing it on to his son. Such a perspective is typical within patrilineal societies such as China, where the son preference is the norm (see Murphy et al 2011;Lin and Mac an Ghaill 2017). Yang Dong's account also highlighted the economic marginalization and the negotiation of a good father.…”
Section: Migrant Fathers Inter-generational Supports and Filial Pietymentioning
confidence: 97%
“…He believed that buying a fangzi (house/apartment) would enable him to make a masculine achievement as a father through passing it on to his son. Such a perspective is typical within patrilineal societies such as China, where the son preference is the norm (see Murphy et al 2011;Lin and Mac an Ghaill 2017). Yang Dong's account also highlighted the economic marginalization and the negotiation of a good father.…”
Section: Migrant Fathers Inter-generational Supports and Filial Pietymentioning
confidence: 97%
“…Most of them acknowledged that they would choose for their parents to come to a European country, stay in Europe temporarily and then go back to China after acquiring work experience. Lin and Ghaill (2017) further concluded that men assume responsibility for the family more than women in patriarchal Chinese society. Most female participants said they would return and support their parents as they get older.…”
Section: Fig 3 Selective Codingmentioning
confidence: 99%
“…This shows that in the United States, the consequences of failing to conform will be even more serious than being regarded as homosexual. What's more, the existence of campus bullying makes the stereotypic notions of masculinity and femininity more compulsive, even cause emotional disturbance and self-injurious behaviors four times more than girls [6], strengthening the severity of the boy crisis [5].…”
Section: Behavior Of the "Boy Crisis"mentioning
confidence: 99%
“…Developing countries also face similar problems. In China, the crisis includes boys' academic failure, bodily health, mental health, and social adaptation [6]. Therefore, the "boy crisis" has been a serious global problem that needs analysis and solutions.…”
Section: Gender Gap In Achievementmentioning
confidence: 99%